Autologous Alternatives to Facial Transplantation - Gottlieb, Lawrence; Agarwal, Shailesh (Journal of Reconstructive Microsurgery, 2012)
Advances in autologous reconstructive concepts, principles, and techniques allow us to close wounds of almost any size. The concept of three-dimensional (3-D) functional units of the face is discussed. Five cases of facial deformity are presented to demonstrate the concept of reconstructing different “functional” units of the face with consideration for restoring the 3-D loss of tissue within the anatomic boundaries of the aesthetic units. This article demonstrates that most individual parts or functional units can be reconstructed with autologous techniques in an acceptable way. It is when large segments of multiple contiguous functional units are destroyed that these techniques fall short of rebuilding parts that function harmoniously with the rest of the face.
Keywords: autologous reconstruction; functional units; composite tissue allotransplantation